2021
DOI: 10.1111/jcal.12587
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an automated feedback program for a foreign language writing course: A learner‐centric study

Abstract: Considering the prominence attached to written corrective feedback (WCF) within the domain of second/foreign language (L2) acquisition, automated writing evaluation (AWE) tools have steadily gained ground over the last two decades. The current study was an attempt to investigate the extent incorporating an AWE program, known as Criterion®, within a process writing framework would affect learners' writing quality in an English as a foreign language context. Moreover, we drew a comparison between the overall eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A considerable number of empirical studies have investigated AWE’s effectiveness in improving writing but produced mixed findings. Most showed positive results (e.g., Cheng, 2017; Chew et al, 2019; Hassanzadeh & Fotoohnejad, 2021), while some reported null or insignificant effects (e.g., Wilson & Czik, 2016; Wilson & Roscoe, 2020). For instance, Cheng (2017) investigated the impact of online automated feedback (OAF) on the quality of EFL students’ reflective journals at the university level and found that students receiving OAF outperformed their counterparts under traditional instruction in terms of the overall score and demonstrated a significant improvement in writing quality.…”
Section: Empirical Studies Examining Awe’s Effectiveness On Writing Q...mentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of empirical studies have investigated AWE’s effectiveness in improving writing but produced mixed findings. Most showed positive results (e.g., Cheng, 2017; Chew et al, 2019; Hassanzadeh & Fotoohnejad, 2021), while some reported null or insignificant effects (e.g., Wilson & Czik, 2016; Wilson & Roscoe, 2020). For instance, Cheng (2017) investigated the impact of online automated feedback (OAF) on the quality of EFL students’ reflective journals at the university level and found that students receiving OAF outperformed their counterparts under traditional instruction in terms of the overall score and demonstrated a significant improvement in writing quality.…”
Section: Empirical Studies Examining Awe’s Effectiveness On Writing Q...mentioning
confidence: 99%
“…The results revealed that the SW-PAL group demonstrated a greater improvement in summary writing quality compared with their conventional counterparts. Hassanzadeh and Fotoohnejad (2021) examined the efficacy of incorporating Criterion in an EFL classroom by comparing the effects of AWE and teacher-generated feedback. Their results showed that AWE feedback was more efficient in improving the overall quality of writing than feedback from teachers over time.…”
Section: Empirical Studies Examining Awe’s Effectiveness On Writing Q...mentioning
confidence: 99%
“…According to Lipsey and Wilson (2001, p. 108), the potential outliers that were ‘more than three standard deviations from the mean of all effect sizes’ should be excluded. As such, one selected research ( g = 3.607, Hassanzadeh & Fotoohnejad, 2021) out of the 26 eligible studies that yielded extremely large effect size was excluded, resulting in 25 remaining primary studies that yielded 33 effect sizes for the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, several experiments to utilize AWE reported mixed results. For example, in an Iranian context, AWE integration resulted in significant student writing progress (Hassanzadeh & Fotoohnejad, 2021). In another study, students' grammatical knowledge increased while their writing apprehension decreased (Waer, 2021).…”
Section: Introductionmentioning
confidence: 95%